Classificação de Automorfismos de Grupos Finitos - Albuquerque, Flávio Alves de (2011)
In this paper we study finite Abelian groups, where state and prove the fundamental theorem of finitely generated abelian groups, as well as determine a characterization of automorphisms of a p-group, moreover, we exhibit an algorithm that determines the count of the number of automorphisms of p-groups. Finally, we show the automorphisms of the non-Abelian dihedral group.